A single chassis integrated machine system for transplanting oil palm seedlings - Roodi, Siamak Moslehi (2011)
The current technology employed by the plantation industry in the planting and replanting of oil palm seedlings are very laborious and time consuming. The whole planting operation involves many activities done inconsistently by workers. A single chassis integrated wheeled machine system was designed and tested for the planting of oil palm seedlings in plantations The identification and marking of planting points was done using a portable hand held Real Time Kinematic Global Positioning System (RTK GPS) unit. Field evaluation was conducted to determine the accuracy of using RTK GPS unit in laying the seedling planting points in the plantation field. The registered measurement spacing distance errors between adjacent planting points and between alternate planting rows are 5.1±0.020 cm and 0.40±0.022 cm, respectively. The two-man operated machine integrated all the 6 activities in a planting operation. The complete machine consists of a universal prime mover and a transplanter unit, with a configuration consisting of a seedling bin, support sleeves, planting assembly, operator compartment and hydraulic system. This four wheel drive and four steer prime mover is equipped with a Kubota V-3300 4 cylinder water cooled 50.7 KW @ 2600 rpm diesel engine, Sauer Danfoss Series 40 axial piston main hydrostatic pump with 46cm3/rev displacement @ 210 bar continuous pressure, oscillating front and rear axles, and 4 units of Bobcat heavy duty 12 ply 12-16.5 tires. The driver drives and then stops machine system at the already marked planting point in the field and the operator behind operates the hydraulic controls of the transplanter unit for the seedling planting operation. Upon completing the planting activities at the planting point, the driver then moves the machine system to the next planting point within the planting row and the operator repeats back the planting processes until all the planting points within the planting row were planted with the seedlings. Upon completing the planting operation for the planting row the driver moves back the machine to the nearby seedling supplying point for loading new batches of seedlings on to the machine system in order to continue back the planting operation on the next planting row. The machine system seedling bin is designed to accommodate a maximum of 28 palm seedlings per machine trip and this number of seedlings is enough to cater the number of available planting points within a planting row for any standard oil palm plantation layout in Malaysia. Field evaluation and testing with the machine system shows this mechanized planting system has a planting capacity of 120 seedlings/man-day or 0.75 ha/man-day, and planting cost of RM0.84/seedling. The seedling planting in the oil palm plantation by using machine system required a total 7.90 Kcal/min-man human energy and the current manual employed method of seedling planting in the oil palm plantation required a total 17.10 Kcal min-1 man-1 human energy. The human energy for machine system is 46 percent less than manual method. Assessment on the planting quality of the planted seedling shows percentage in planting success of 99.25%, leaning angles of 86.04±0.29 degree, spacing deviation of 5±4.14 cm, row lignment of 4.55±0.24 cm, and pulling forces of the planted seedlings to be 380.8±23.72 N. Conclusively, an increased in the planting capacity per man-day of 1.21 times with this machine system over the trailed type machine system while an increased in the planting capacity per man-day of 2.14 times was obtained with this machine system over the manual method. A planting cost reduction per seedling of 28.81 percent or cost saving of 0.34RM per seedling was obtained with the machine system over the trailed type system, and planting cost reduction per seedling of 44.37 percent or cost saving per seedling of 0.67 RM was obtained with the machine system over the manual method based on the field observation. The average total time moving machine system between planting points with RTK GPS was 118.58 second, and the average total time moving machine system between planting points without RTK GPS was 30.38 second.